Extensive 5'-surveillance guards against non-canonical NAD-caps of nuclear mRNAs in yeast - Zhang, Yaqing; Kuster, David; Schmidt, Tobias Thomas; Kirrmaier, Daniel; Nübel, Gabriele; Ibberson, David; Benes, Vladimir; Hombauer, Hans; Knop, Michael; Jäschke, Andres (Nature Communications, 2020)
The ubiquitous redox coenzyme nicotinamide adenine dinucleotide (NAD) acts as a non-canonical cap structure on prokaryotic and eukaryotic ribonucleic acids. Here we find that in budding yeast, NAD-RNAs are abundant (>1400 species), short (<170 nt), and mostly correspond to mRNA 5′-ends. The modification percentage of transcripts is low (<5%). NAD incorporation occurs mainly during transcription initiation by RNA polymerase II, which uses distinct promoters with a YAAG core motif for this purpose. Most NAD-RNAs are 3′-truncated. At least three decapping enzymes, Rai1, Dxo1, and Npy1, guard against NAD-RNA at different cellular locations, targeting overlapping transcript populations. NAD-mRNAs are not translatable in vitro. Our work indicates that in budding yeast, most of the NAD incorporation into RNA seems to be disadvantageous to the cell, which has evolved a diverse surveillance machinery to prematurely terminate, decap and reject NAD-RNAs.